2019
DOI: 10.1111/jvh.13049
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hepatitis E virus infection among blood donors in a high endemic area of Central Italy

Abstract: Summary In Europe, autochthonous hepatitis E virus (HEV) infection is mainly a foodborne zoonosis, but it is also transmitted by blood transfusion. Despite the numerous prevalence surveys, only a few studies have investigated HEV incidence. We aimed to determine HEV incidence and risk factors among blood donors in a hyperendemic area in Central Italy. Of 296 blood donors who had tested HEV negative in two previous seroprevalence surveys in L'Aquila, 198 agreed to undergo at least another blood sampling for est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The virus circulates widely in Italy in the human population as proved by several studies on the detection of antibodies against HEV in blood donors [ 27 , 28 , 29 , 30 ]. At the national level, the mean seroprevalence in blood donors is 8.7% with a highly variable range depending on geographical area investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus circulates widely in Italy in the human population as proved by several studies on the detection of antibodies against HEV in blood donors [ 27 , 28 , 29 , 30 ]. At the national level, the mean seroprevalence in blood donors is 8.7% with a highly variable range depending on geographical area investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Both regions are not the main areas of pig farming, mostly located in Northern Italy, where the mean seroprevalence in humans varies between 5 and 10%. The observed high seroprevalence in these hyperendemic regions in Central Italy was deemed to be linked to eating habits such as consumption of raw liver sausages [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…On review of full‐text articles for the remaining 140 citations, 83 did not meet selection criteria. Of the 57 citations selected for final data synthesis , one provided three data sets ; hence, we had a total of 59 data sets from 28 countries (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that antibody levels decrease over time and in some subjects, anti-HEV IgG can disappear after a follow-up ranging between 1 and 22 years [51]. A recent study among blood donors from central Italy using the Wantai assay has reported an HEV seroconversion rate of 2.1 per 100 person-years [52], in the same order of magnitude (1.3-4.6/100 person-years) as those estimated with our models.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies in Europe, conducted with the Wantai serological test, showed great geographical heterogeneity of anti-HEV carriers with seroprevalences ranging from 5-6% in Scotland [29,30] to 52% in south-western France [31]. Important variability was observed even within individual countries [32][33][34]. A nationwide seroprevalence study conducted in France reported a 22% anti-HEV IgG seroprevalence in the French blood donor population tested in 2011 and 2012 [32].…”
Section: Introductionmentioning
confidence: 99%